2014
DOI: 10.3892/mmr.2014.2088
|View full text |Cite
|
Sign up to set email alerts
|

Thoc1 inhibits cell growth via induction of cell cycle arrest and apoptosis in lung cancer cells

Abstract: THO complex 1 (Thoc1) is a human nuclear matrix protein that binds to the retinoblastoma tumor suppressor retinoblastoma protein (pRb). While some studies suggest that Thoc1 has characteristics of a tumor suppressor protein, whether Thoc1 can inhibit lung cancer cell growth is not clear. In the present study, we observed that Thoc1 is lowly expressed in the lung cancer cell lines SPC-A1 and NCI-H1975. Then, we investigated the potential effects of Thoc1 on lung cancer cell proliferation, cell cycle and apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…GO enrichment analysis revealed that changes in the most significant module were mainly enriched in ‘cell division’, ‘mitotic nuclear division’ and ‘G 2 /M transition of mitotic cell cycle’, while changes in KEGG analysis were mainly enriched in the ‘cell cycle’ and ‘p53 signaling pathway’. Previous studies demonstrated that dysregulation of the cell cycle is associated with carcinogenesis and the progression of tumors (32,33). In the current study, a PPI network consisting of 44 nodes and 886 edges was constructed.…”
Section: Discussionmentioning
confidence: 99%
“…GO enrichment analysis revealed that changes in the most significant module were mainly enriched in ‘cell division’, ‘mitotic nuclear division’ and ‘G 2 /M transition of mitotic cell cycle’, while changes in KEGG analysis were mainly enriched in the ‘cell cycle’ and ‘p53 signaling pathway’. Previous studies demonstrated that dysregulation of the cell cycle is associated with carcinogenesis and the progression of tumors (32,33). In the current study, a PPI network consisting of 44 nodes and 886 edges was constructed.…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation and apoptosis are dynamically balanced processes, and an imbalance between them leads to the malignant transformation of cells and tumorigenesis (19). Ki67 is a proliferation-related protein; cleaved caspase-9 is the apoptotic initiator and cleaved caspase-3 is the executor of apoptosis (20,21). The present findings indicated that, following the knockdown of SLCO4C1, proliferation was inhibited and apoptosis was induced.…”
Section: Discussionmentioning
confidence: 51%
“…THOC1 deficiency leads to defects in transcription elongation and pre-mRNA export [ 8 , 9 ] and accumulation of R-loops, resulting in genome instability [ 10 ]. Increasing evidence demonstrates that THOC1 expression is elevated in many human cancers, such as prostate [ 11 ], colorectal [ 12 ] and lung cancers [ 13 ], and associated with poor prognosis. However, THOC1 expression and its prognostic significance in HCC remains unknown.…”
Section: Introductionmentioning
confidence: 99%